Relationship between spiritual health and quality of life in patients with T2DM - Valderrama Ruiz, Daniel Alberto; Riquelme-Heras, Héctor; Valderrama Ruiz, Laura Isabel; Sierra , Irasema; Gutierrez-Herrera, Raúl (Revista Cuidarte, 2026)
Highlights • This study identified a positive and statistically significant correlation between spiritual health and health-related quality of life (HRQoL) in patients with type 2 diabetes treated in three hospitals in Nuevo León, Mexico in 2024. • This institutional gradient suggests that environments with structured spiritual integration enhance subjective outcomes such as quality of life and emotional well-being. • Young adults and those who did not use insulin reported better health-related quality of life. • The results contribute to the understanding of the role of spirituality in type 2 diabetes, laying the groundwork for longitudinal studies and interventions. Introduction: Type 2 diabetes mellitus is a chronic disease that impacts health-related quality of life. Spiritual health may positively influence patients’ well-being, being a relevant aspect for improving comprehensive management. Objective: To assess the relationship between spiritual health and health-related quality of life in patients with type 2 diabetes mellitus, aiming to provide evidence to support interventions integrating medical and spiritual aspects. Materials and Methods: A cross-sectional study conducted in 2024 with 230 patients from three hospitals. Spiritual health was measured using the ESE-UM scale, and health-related quality of life with the D-39 questionnaire. Spearman’s correlation and non-parametric tests were used to analyze associations with sociodemographic (age, sex, socioeconomic status) and clinical factors (insulin use, disease progression). Results: A significant positive correlation was found between spiritual health and health-related quality of life (ρ=0.338, p < 0.001). Women and patients with high socioeconomic status reported greater spiritual health, while younger adults and those not using insulin showed better health-related quality of life. Discussion: The findings confirm that spiritual health serves as a coping resource in type 2 diabetes mellitus, enhancing health-related quality of life, consistent with prior studies. Factors such as sex, socioeconomic status, and hospital setting influenced both variables. Conclusions: Spiritual health significantly improves health-related quality of life in type 2 diabetes mellitus patients, influenced by sex, socioeconomic status, and hospital environment. Incorporating spiritual care into type 2 diabetes mellitus management could optimize clinical and well-being outcomes, considering these sociodemographic variables. How to cite this article: Valderrama Ruiz Daniel Alberto, Riquelme-Heras Héctor, Valderrama Ruiz Laura Isabel, Sierra Iracema, Gutierrez-Herrera Raúl. Relationship between spiritual health and quality of life in patients with type 2 diabetes. Revista Cuidarte. 2026;17(2):e5149. https://doi.org/10.15649/cuidarte.5149